A combined experimental-numerical investigation of two-phase self-cleaning drop modulation by amphiphilic component addition - Kumar, Shreyas Vijayendra; Ström, Henrik (Frontiers in Chemical Engineering, 2025)
Industrial plate heat exchangers for cooling of complex, condensing gas mixtures are possible to operate in a self-cleaning mode if a stable flow of small, spherical-like, motile drops can be realized over the heat transfer surfaces. Here, we investigate the effects of adding an amphiphilic component (benzoic acid) to a pure air/water system in terms of providing the necessary prerequisites for such a functionality. The equilibrium apparent (static) advancing and receding contact angles are measured experimentally at varying inclinations and used to inform multiphase direct numerical simulations using the Volume-of-Fluid method. The simulations enable quantification of the distortion of drops caused by the combined gas-liquid-plate interaction in the presence of flow. It is found that the addition of benzoic acid lowers the apparent contact angles, and that the magnitude of this effect is dependent on the plate surface treatment – being more pronounced on a hydrophobically modified plate than on a hydrophilically modified one. The addition of benzoic acid increases the wetting of the drop on the surface and decreases the flow-exposed gas-liquid interface, although both these effects are relatively modest in magnitude. It is suggested that two-phase heat exchangers relying on self-cleaning mechanisms are relatively immune to the presence of low concentrations of amphiphilic impurities that are chemically similar to benzoic acid. The present work thus highlights the role of combined experimental-numerical approaches to gain insight into process phenomena that are not readily amenable to only experiments or only modeling.